2022
DOI: 10.1186/s40644-022-00462-6
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of cervical nodal necrosis on staging imaging of nasopharyngeal carcinoma in era of intensity-modulated radiotherapy: a systematic review and meta-analysis

Abstract: Purposes To systematically review and perform meta-analysis to evaluate the prognostic value of cervical nodal necrosis (CNN) on the staging computed tomography/magnetic resonance imaging (MRI) of nasopharyngeal carcinoma (NPC) in era of intensity-modulated radiotherapy. Methods Literature search through PubMed, EMBASE, and Cochrane Library was conducted. The hazard ratios (HRs) with 95% confidence intervals (CIs) of CNN for distant metastasis-free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 45 publications
1
0
0
Order By: Relevance
“…The incidence rate of LNN in stage N1-3 NPC patients was 32.4% in this study, similar to 23-42% reported in previous studies 8 , 26 - 27 . This study further evaluated the incidence of LNN at different N stages, that was 25.1% with N1, 47.9% with N2, and 52.7% with N3.…”
Section: Discussionsupporting
confidence: 90%
“…The incidence rate of LNN in stage N1-3 NPC patients was 32.4% in this study, similar to 23-42% reported in previous studies 8 , 26 - 27 . This study further evaluated the incidence of LNN at different N stages, that was 25.1% with N1, 47.9% with N2, and 52.7% with N3.…”
Section: Discussionsupporting
confidence: 90%